2016
DOI: 10.1186/s40001-016-0232-y
|View full text |Cite|
|
Sign up to set email alerts
|

Cytokine and human leukocyte antigen (HLA) profile for graft-versus-host disease (GVHD) after organ transplantation

Abstract: BackgroundGraft-versus-host disease (GVHD) after liver and kidney transplantation has high mortality and causes diagnostic challenges. This study aims to describe the cytokine and human leukocyte antigen (HLA) profile in the GVHD after liver and kidney transplantation.MethodsA high-throughput detection kit was applied and altogether 18 different cytokines were tested simultaneously. GVHD patients included 23 post-liver transplantation patients; 22 post-renal transplantation patients; The control patients inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Toll-like receptor-4 (TLR-4) has been increasingly recognized as playing a critical role in the pathogenesis of I:R injury of renal grafts [42, 43], and research into anti-TNF agents have shown promise with regards to being protective against I:R injury in animal models [21]. Additionally, we identified pathways associated with common immunologic processes affecting renal transplantation and rejection, such as graft-versus-host disease [44], natural killer cell-mediated toxicity [45], Jak-STAT signaling [46], peroxisome proliferator-activated receptor signaling [47], chemokine signaling, and allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptor-4 (TLR-4) has been increasingly recognized as playing a critical role in the pathogenesis of I:R injury of renal grafts [42, 43], and research into anti-TNF agents have shown promise with regards to being protective against I:R injury in animal models [21]. Additionally, we identified pathways associated with common immunologic processes affecting renal transplantation and rejection, such as graft-versus-host disease [44], natural killer cell-mediated toxicity [45], Jak-STAT signaling [46], peroxisome proliferator-activated receptor signaling [47], chemokine signaling, and allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Exaggerated cytokine response of IL 2, IL 18, and IFN-g occurs during GVHD have been used to predict the occurrence of GVHD early. 11 Chimerism is the presence of donor lymphocytes in the recipient's peripheral blood, skin, or bone marrow. Donor T cell chimerism peaks around the first week after LT and reduces to <1% by 4 weeks, confirm-ing donor engraftment.…”
Section: Diagnosismentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors requested a correction in the presentation of their institutions as they appear on the Web of Science. Specifically, it should be emphasized that the institutions belong to Zhejiang University.…”
Section: Erratum To: Eur J Med Res (2016) 21:38 Doi 101186/s40001-01mentioning
confidence: 99%